A randomized trial of exercise and diet on health‐related quality of life in survivors of breast cancer with overweight or obesity. Issue 20 (23rd June 2021) - Brown, Justin C.; Sarwer, David B.; Troxel, Andrea B.; Sturgeon, Kathleen; DeMichele, Angela M.; Denlinger, Crystal S.; Schmitz, Kathryn H.
Abstract : Background: Obesity is a chronic, relapsing, and progressive disease; it is associated with poor health‐related quality of life (HRQOL) in survivors of breast cancer. Methods: In this 2 × 2 factorial trial, 351 survivors of breast cancer with overweight or obesity were randomized to 1 of 4 treatment groups for 52 weeks: control, exercise alone, diet alone, or exercise plus diet. HRQOL end points were measured at baseline and at week 52 using the 36‐Item Medical Outcomes Survey‐Short Form (SF‐36). Repeated measures analysis of covariance quantified the estimated treatment difference (ETD). Results: At baseline, participants had a mean (SD) age of 59.4 years (8.7), body mass index of 34.0 kg/m 2 (5.9), and 71 participants (20.2%) self‐reported fair or poor general health. After 52 weeks, compared with control, the exercise plus diet improved the physical health summary score (ETD: 5.39; 95% CI, 0.55‐10.22); exercise alone (ETD: –1.91; 95% CI, –6.60 to 2.79) and diet alone (ETD: 3.16; 95% CI, –1.52 to 7.83) did not change the physical health summary score. Compared with control, exercise alone (ETD: –0.27; 95% CI, –6.60 to 2.79), diet alone (ETD: 3.25; 95% CI, –1.41 to 7.91), and the exercise plus diet (ETD: 1.75; 95% CI, –2.90 to 6.39) did not change the mental health summary score. Exercise alone did not impact any HRQOL subscale; diet alone improved the vitality subscale; exercise plus diet improved the physical functioning, role—physical and vitality subscales. Conclusion: In survivors of breast cancer with overweight or obesity, exercise plus diet improved select HRQOL end points at week 52. Abstract : Obesity is associated with poor health‐related quality of life in survivors of cancer. In survivors of breast cancer with overweight or obesity, exercise plus diet improved select health‐related quality of life end points at week 52.